2010
DOI: 10.4049/jimmunol.1000863
|View full text |Cite
|
Sign up to set email alerts
|

Complement C3a, CpG Oligos, and DNA/C3a Complex Stimulate IFN-α Production in a Receptor for Advanced Glycation End Product-Dependent Manner

Abstract: The receptor for advanced glycation end products (RAGE) is a multiligand transmembrane receptor implicated in a number of diseases including autoimmune diseases. To further understand the pathogenic mechanism of RAGE in these diseases, we searched for additional ligands. We discovered that C3a bound to RAGE with an EC50 of 1.9 nM in an ELISA, and the binding was increased both in magnitude (by >2-fold) and in affinity (EC50 70 pM) in the presence of human stimulatory unmethylated cytosine-guanine-rich D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…Second, RAGE expression is upregulated in the kidneys of SLE patients (23), and signaling through HMGB1-RAGE activates mesangial cells in vitro, therefore suggesting a role for the RAGE axis in the progression of lupus nephritis (24). Furthermore, other alarmin molecules such as C3a as well as CpG DNA oligos are able to bind to RAGE and stimulate IFN-a production by human PBMCs in a RAGE-dependent manner (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Second, RAGE expression is upregulated in the kidneys of SLE patients (23), and signaling through HMGB1-RAGE activates mesangial cells in vitro, therefore suggesting a role for the RAGE axis in the progression of lupus nephritis (24). Furthermore, other alarmin molecules such as C3a as well as CpG DNA oligos are able to bind to RAGE and stimulate IFN-a production by human PBMCs in a RAGE-dependent manner (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…C3a was also shown to bind to the receptor for advanced glycosylation end-products (RAGE) with a high affinity, but this interaction is more complex than a simple ligand-receptor interaction (29,30). Ruan et al (29) demonstrated that C3a is able to form a complex with CpG oligonucleotides to enhance IFN-a release from mononuclear leukocytes.…”
mentioning
confidence: 99%
“…The syndrome has also been linked to increased risk of developing preeclampsia and other pregnancy complications such as IUGR and fetal loss 89,90 . In mouse models, complement has been shown to be pivotal to the pregnancy complications associated with APS, as inhibition of C3 cleavage, through the use of C3-deficient animals of C3 convertase inhibitors, can prevent the growth restriction and fetal loss 87,91,92 .…”
Section: C1qmentioning
confidence: 99%
“…However, although the pharmacology of SB290157 may be controversial, the conclusion drawn by the authors may now be reinterpreted to take into account the acute 'anti-neutrophil' effects of C3aR discovered recently 47 . It is uncontroversial that, at least at the level of the nephron, C3aR is involved in the pathogenesis of renal disease, including the induction of metaplasia in nephron epithelial cells central to the disease 91,92 . These actions appear synergistic to the role of C5aR1 at the tissue level, but may be redundant in the presence of 69 elevated C5a concentrations, which is much more potent than C3a as a pro-inflammatory mediator at the receptor level.…”
Section: (Iii) Renal Diseasementioning
confidence: 99%
See 1 more Smart Citation